Minjian : the rise of China's grassroots intellectuals - Veg, Sebastian (Global Chinese culture., 2019)
"Veg argues that a new type of intellectual appeared in post-Tiananmen China. Breaking with the universalist, enlightenment paradigm of the 1980s, as well as with the older, traditional figure of the advising and dissenting literati, intellectuals who came of age in the 1990s no longer indulged as frequently in sweeping discourses about culture, the nation, or democracy. Their legitimacy derived from their work with "vulnerable groups," and their shared experience with marginal realms of society. These "grassroots intellectuals" are not simply activists, however. They engage in a public discourse that relies on their specific knowledge, relying on the embryonic and always endangered public sphere that has appeared in China during this time. Moreover, they define themselves as separate both from the state and from the market, positing instead a third sector of activity"--